PENCEGAHAN INVESTASI BODONG MELALUI EDUKASI KEUANGAN KEPADA REMAJA KARANG TARUNA PAGERE, KELURAHAN PABUARAN, PURWOKERTO UTARA - Ascaryan Rafinda; Agus Suroso; Eliada Herwiyanti (Jurnal Pengabdian Bisnis dan Akuntansi Soedirman (JPBA), 2023)
Karangtaruna is a place for youth groups to carry out self-actualization. Social and business activities are the main activities in the Karangtaruna group. Social activities such as competitions, community service and helping community activities. While business activities such as opening a business and helping the business of the surrounding community. Karang Taruna Pagere youth who live in Pabuaran RT 01 RW 04 have a great desire to learn about investment because many people are trapped in fake investments. A lack of resources in the form of knowledge about investment in general and fraudulent investment constraints this great desire. The output of this activity is the increase in the value of investment knowledge from members of Karangtaruna Pagere at RT 01 RW 04, Pabuaran Village, Purwokerto. The results showed that the results of the investment knowledge test on the pre-test were 54%, and the post-test results were 86%. This increase was also followed by many socialization programs from Karangtaruna members to the public regarding investment education